Les textes de Cerquand. Les contes qui n'existent pas - Zaika, Natalia M. (Anuario del Seminario de Filología Vasca "Julio de Urquijo", 2009)
Our article is about the Basque stories that Jean-François Cerquand published between 1875 and 1882 in the Bulletin de la Société des Sciences, Lettres et Arts de Pau. The principles of the collection as stated in the comments (the fidelity to the text) are described, as well as the results obtained by Cerquand, which do not correspond to those principles. Many digressions, expansions and modifications are characteristic of the texts translated into French. If the translations of the first parts are relatively true to the Basque texts, the reader will find the most considerable changes in the fourth part. Having analysed the difference between the first parts and the fourth, as well as some comments in the third and fourth parts about the reception of the traditional text, one reaches the conclusion that Cerquand was the one who modified the translation of the texts of the stories sent by the teachers.